A Rare Case Report of Spontaneous Disassembly of Bipolar Hip Prosthesis in Elderly Patient - Shah, Ruchit (J Orthop Case Rep, 2020)
INTRODUCTION: Hip fracture is an established health problem, especially in the elderly population and, its incidence is dramatically rising in the globe. The standard protocol of management in the elderly population for end-stage hip diseases and unstable femur fracture is bipolar hemiarthroplasty. Common complications of hip replacement include infection, fracture, dislocation, venous thrombosis, nerve palsy, chronic pain, and implant failure. In the literature, there are very few reported cases of disassembly of the implant in hemi replacement arthroplasty. CASE REPORT: We, hereby, present a case of the spontaneous disassembly of the bipolar hip prosthesis, which was timely recognized and treated adequately in an elderly patient. CONCLUSION: The use of the cemented bipolar prosthesis can also lead to disassembly of the implant components and thereby the need for open reduction. Identification of the distinction between dislocation of head and disassembly of the prosthetic components is vital for favorable patient prognosis.